ANALYZING FACTORS AFFECTING INDONESIA'S FOREIGN EXCHANGE RESERVES FOR THE 2012-2021 PERIOD - Ruslan, Nining Ruslan; Leasiwal, Teddy Christianto; Louhenapessy, Desry J.; Hanoeboen, Bin Raudha Arif; Sapteno, Fibryano; Laitupa, Abdul Aziz (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
This research analyzes the effect of exchange rates, exports, and imports on Indonesia's foreign exchange reserves in the 2012-2021 period. The independent variables in this study are exchange rates, exports, and imports, while the dependent variables are Indonesia's foreign exchange reserves. The data used in this study was obtained from the official websites of the Central Statistics Agency (BPS), Bank Indonesia, and Worldbank in 2023. The data analysis method used is the Vector Error Correction Model (VECM) which is a derivative of Vector Autoregression (VAR) analysis. The data collection technique used is secondary data with quantitative research type. The results of the VECM analysis show that the exchange rate (exchange rate) has a significant effect on Indonesia's foreign exchange reserves, exports have a significant positive influence in the long run on foreign exchange reserves, while imports have a significant effect on foreign exchange reserves. Therefore, it can be concluded that international trade has a significant influence on Indonesia's foreign exchange reserves, and exchange rates, exports, and imports are important factors affecting Indonesia's foreign exchange reserves. Keywords: Exchange Rate, Export, Import, Foreign Exchange Reserves